Amelogenesis Imperfecta Enamel Changes, Amelogenin, and Dental Caries Susceptibility - Vieira, Alexandre R.; Modesto, Adriana (Frontiers in Dental Medicine, 2020)
There is great interest in identifying the subset of individuals in the population that are more susceptible to dental caries. We proposed that a portion of these particular individuals are more susceptible to dental caries due to changes in dental enamel that are related to amelogenin genomic variation. However, apparently amelogenin function can be impacted by inflammation, and this can lead to small changes in the structure of the dental enamel that later in life increases the risk of dental caries.